Hemispheric asymmetries of the Venus plasma environment. Issue 7 (11th July 2013) - Jarvinen, R.; Kallio, E.; Dyadechkin, S.
Abstract : [1] We study the Venus‐solar wind interaction and the hemispheric asymmetries of the Venus plasma environment in the global HYB‐Venus hybrid simulation. We concentrate especially on the role of the flow‐aligned interplanetary magnetic field (IMF) component (i.e., the Parker spiral angle or the IMF cone angle) and analyze the dawn‐dusk and E sw asymmetries between four magnetic quadrants around Venus. Using the simulation model, we study two upstream condition cases in detail: the perpendicular IMF to the solar wind flow case and the nominal Parker spiral case (dominant flow‐aligned IMF component). Several differences and similarities were found in these two simulation runs. Common features of the Venus plasma environment between the two cases include asymmetric magnetic barrier and tail lobes and asymmetric planetary ion escape in the direction of the solar wind convection electric field. Further, protons of planetary origin and of solar wind origin were found to follow similar velocity patterns in the Venus plasma wake in both cases. The differences when the IMF flow‐aligned component is dominating compared to the perpendicular IMF case, the so‐called (magnetic) dawn‐dusk asymmetries, include the parallel bow shock and the foreshock region, the asymmetric magnetic barrier, the asymmetric tail current system, and the asymmetric central tail current sheet. Further, the escaping planetary H + and O + ion fluxes are concentrated more on the hemisphere of the parallel bow shock. When interpreting in situ plasma and magnetic observations from Venus, the features of at least these two basic IMF configurations should be considered. Key Points: Venus plasma environment is hemispherically remarkably asymmetric Asymmetries are due to solar wind electric field and IMF flow‐aligned component The IMF flow‐aligned component affects interpretation of in situ observations